The role of community-based organizations in improving rural female adolescents’ knowledge, attitude, and haemoglobin level - Apriningsih, Apriningsih; Ismail, Rita; Ciptaningtyas, Ratri; Sugiyatmi, Tri Astuti; Angkasa, Dudung; Nadheem, Fathimath Ana (Intelektual Pustaka Media Utama, 2025)
Addressing the prevalence of anemia in female adolescents requires the active engagement of multiple sectors. The COVID-19 pandemic has hampered the school-based weekly iron folate supplementation (WIFAS) program which may lead to an increased anemia prevalence in female adolescents. The role of community-based organizations in assisting preexisting programs is supposed to alleviate the prevalence effectively. This study aimed to analyze the role of a community-based organization (CBO) consisting of youth organizations and integrated services post cadres in a program to improve hemoglobin level in Sirnagalih Village, Bogor, West Java, Indonesia. This pre-experimental study involved 89 female adolescents. After the intervention conducted by the CBO, significant differences were identified in the level of knowledge, attitudes, and hemoglobin (Hb) levels of female adolescents (p<0.05). The linear regression test obtained a statistical model equation related to female adolescents' Hb levels after being assisted by the CBO (R = 0.821, p = 0.000). The variable role of CBO, understanding media information, initial Hb level, adherence to consuming WIFAS, and habits to consume iron enhancer food of female adolescents can explain the Hb levels as much as 82%.